Islamic banking and derivative financial instruments (Journal of Economic Research & Business Administration, 2016)
Methodological base of research in given clause was made with modern concepts Islamic banking and Islamic model of financing takaful (in surance) as a whole. Findings: the results indicate the mathematical model consists of a probability space, a Brownian motion and a Poisson process. The jumps are independent and identically distributed. The approach con sists of defining a notion of risk and production instrument takaful (insur ance) in order to minimize the risk.Originality/value: In new judgement the principle «riba» an islam breaking moral laws as an interdiction of usury and its significant advantages in any spheres of human life is shown; The author’s financial analysis of economic experience Islamic bank ing in the countries of near and far abroad as new judgement of Islamic bank system is lead; In a new context features of financial specificity Islamic model of financing takaful (insurance) in modern Kazakhstan are revealed.